Anxiety Symptoms and Associated Factors Among Chronic Low Back Pain Patients in China: A Cross-Sectional Study - Hu, Yueming; Yang, Zechuan; Li, Yong; Xu, Yong; Zhou, Xuan; Guo, Ningfeng (Frontiers in Public Health, 2022)
Background This study aimed to investigate the prevalence of anxiety symptoms among patients with chronic low back pain and explore its related factors. Methods A cross-sectional study was conducted on patients with chronic low back pain from two general hospitals in China. Anxiety symptoms were assessed by the Generalized Anxiety Disorder-7. Binary logistic regression was used to examine the association between demographic characteristics, pain severity, pain self-efficacy, family functioning and anxiety symptoms. Results This study involved 1,172 chronic low back pain patients, with an effective rate of 94.67%. The prevalence of anxiety symptoms among patients with chronic low back pain in China was 23.89%. In the binary logistic regression, patients with more severe pain (OR = 1.15, 95%CI: 1.11–1.18) and pain duration between 1~5 years (1~3 years: OR = 2.45, 95%CI: 1.38–4.36; 3~5 years: OR = 2.99, 95%CI: 1.49–6.00) had a higher risk to anxiety symptoms. In contrast, patients with higher monthly income (OR = 0.62, 95%CI: 0.39–0.98), better family functioning (highly functional family: OR = 0.22, 95% CI: 0.13–0.37; moderately dysfunctional family: OR = 0.44, 95% CI: 0.27–0.72) and higher pain self-efficacy (OR = 0.95, 95%CI: 0.94–0.96) had a lower risk to anxiety symptoms. Conclusion The prevalence of anxiety symptoms among chronic low back pain patients was high in China. Targeted intervention measures should be taken to reduce anxiety symptoms levels of chronic low back pain patients.